Optimizing Passenger Service Administration Through Facility and Resource Improvement: Optimalisasi Administrasi Layanan Penumpang Melalui Peningkatan Fasilitas dan Sumber Daya - Muhammad Abdul Jailani; M. Kasim M; Einsbie Grata Myn; Ahmad Yani (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Standardized passenger service administration is a vital component in airport management to ensure safety, comfort, and user satisfaction; however, its implementation often faces challenges related to resources, infrastructure, and service management. Specific Background: At Juwata International Airport Tarakan, departure, arrival, comfort, value-added services, and terminal capacity management have been aligned with national regulations but still encounter operational constraints. Knowledge Gap: In-depth empirical studies on the supporting and inhibiting factors of passenger service administration at regional airports, particularly in North Kalimantan, remain scarce. Aims: This study analyzes the implementation of passenger service administration and identifies factors influencing service smoothness. Results: Using a descriptive qualitative approach, the findings indicate that regulatory compliance and adequate human resources serve as key enablers, while limited check-in counters, underdeveloped self-check-in facilities, and insufficient supporting amenities are the main obstacles. Novelty: This study provides a comprehensive empirical overview of service dynamics at a regional airport and highlights the urgency of facility innovation. Implications: The findings emphasize the need for optimizing infrastructure, information technology, and human resource management to improve the effectiveness and competitiveness of public services in the air transportation sector. Highlights: Identifies key enablers and obstacles in airport passenger services. Highlights the importance of facility and technology improvements. Emphasizes strategic management for service effectiveness and competitiveness. Keywords: Passenger Service Administration, Airport Management, Service Quality, Infrastructure Optimization, Public Transportation